2021
DOI: 10.1002/jpln.202000465
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological responses and plasticity in Robinia pseudoacacia to the coupling of water, nitrogen and phosphorus

Abstract: Background: Under the background of drought and nitrogen deposition, global climate change is changing the supply of resources and environmental conditions that are crucial to plant growth, and plants respond to climate change by environmentally induced phenotypic changes. Aims: The objective of this study was to assess the differences in the plasticity responses of the morphological, photosynthetic, fluorescence and antioxidant parameters of Robinia pseudoacacia seedlings under water, nitrogen and phosphorus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…In this context, plants grown in the shade partition relatively more nitrogen into the thylakoids, despite lower photosynthetic capacity per unit of nitrogen (Evans, 1989). Similar leaf P n as observed in the present study (<10 μmol m −2 s −1 ) were previously reported when Robinia plants were exposed to drought and nutrient deficiency (He et al, 2016; Su et al, 2021). Furthermore, specific relationship within gas exchange parameters of Robinia plants, for example, between P n and G s , C i , and intrinsic water use efficiency (WUEi) under drought stress, needs to be elucidated in future studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this context, plants grown in the shade partition relatively more nitrogen into the thylakoids, despite lower photosynthetic capacity per unit of nitrogen (Evans, 1989). Similar leaf P n as observed in the present study (<10 μmol m −2 s −1 ) were previously reported when Robinia plants were exposed to drought and nutrient deficiency (He et al, 2016; Su et al, 2021). Furthermore, specific relationship within gas exchange parameters of Robinia plants, for example, between P n and G s , C i , and intrinsic water use efficiency (WUEi) under drought stress, needs to be elucidated in future studies.…”
Section: Discussionsupporting
confidence: 92%
“…Increased ROS production will damage proteins, lipids, carbohydrates and DNA, and finally will result in the interruption of cellular homeostasis and, consequently, in cellular death (Ibrahim et al, 2019). In this context, the effect of drought on ROS generation is indicated by increased contents of malondialdehyde (MDA) and hydrogen peroxide (H 2 O 2 ) (Su et al, 2021). Reduced carbon (C) assimilation and allocation will also impair the synthesis of defense compounds (antioxidants, phenolics) and osmolytes (carbohydrates, amino acids) (Ciais et al, 2005; Leuschner et al, 2001; Liu et al, 2013; Netzer et al, 2016), thereby enhancing the susceptibility to other abiotic and biotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…In maize seedlings under drought, additional nitrogen caused a higher accumulation of chlorophyll a and b and photosynthetic capacity in the leaves (Song et al, 2019). In agreement with the latter, studies across other species and developmental stages support the relationship between chlorophyll and photosynthetic activity under drought stress (e.g., Ahmad et al, 2014;Su et al, 2021;Tariq et al, 2019). Therefore, although no photosynthetic parameters were determined in this study, higher levels of chlorophyll in plants under repeated WDS may have positively impacted plants' photosynthetic performance, thus contributing to the improvement of the plant recovery after the L-WDS.…”
Section: Discussionsupporting
confidence: 64%
“…It has been reported that in the cultivation of Capsicum annuum, the number of flavonoids increases when the plant is inoculated with P. putida because it uses quercetin and kaempferol catabolizing them as a carbon source [34], moreover, it has been observed that S. meliloti responds to the synthesis of proteins, mainly the Nod protein, excreting flavonoids [35]. Furthermore, if the antioxidant capacity is in dynamic equilibrium under normal growth conditions, it implies the decrease of enzymatic activity which results in the elimination of reactive oxygen, however, membrane lipid peroxidation is induced [29], and this could explain the increase of antioxidant capacity in the fruit of C. sativus in our results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the modification of the root structure of a cucumber plant is related to the phytohormone indoleacetic acid (IAA) produced by S. meliloti, A. radioresistens, and P. paralactis [11,14,27]. In addition, it has been reported that S. meliloti and A. radioresistens possess the ability to fix nitrogen and solubilize phosphate, resulting in an increase on the number of late-stage roots and root hairs, since these elements are essential for the plant to increase photosynthetic pigments and proteins, which improves photosynthetic activity and rate, having a positive effect on plant development and a greater accumulation of biomass [28,29]. Furthermore, it has been pointed out that IAA is associated with cell division and differentiation, which improves the structure of the root system [30][31][32].…”
Section: Discussionmentioning
confidence: 99%